UNIT 27.7 Preparation and Use of Reverse Protein Microarrays. Issue 1 (3rd February 2014) - Pin, Elisa; Federici, Giulia; Petricoin, Emanuel F.
Abstract: Reverse‐phase protein array (RPPA) is a multiplex, high‐throughput proteomic technique for profiling the activation status of signal transduction pathways involved in cancer survival and progression, potentially allowing for identification of new biomarkers and drug targets. On RPPA, the entire patient proteome is immobilized on a spot and single proteins can be quantified across a set of samples, spotted on the same array, with high specificity and sensitivity. Array immunostaining and signal amplification systems are used to generate a signal proportional to the concentration of the analyte. Dedicated scanners and software are used to detect spots, measure intensity, subtract background, normalize signal, and generate a numeric value as output. The generated output file is then analyzed using several different bioinformatic and biostatistical tools. In this unit, the RPPA procedure is described in depth, from sample handling and preparation to data analysis, with particular emphasis on tissue sample analysis. Curr. Protoc. Protein Sci . 75:27.7.1‐27.7.29. © 2014 by John Wiley & Sons, Inc.